2nd International Congress on High Performance Sports: A Report on Martial Arts and Combat Sports - Herrera-Valenzuela, T (Idokan Poland Association, 2018)
Introduction. Martial arts and combat sports are practiced by thousands of people around the world and increasingly discussed in scientific publications. Material and Methods. We describe an observational case study by describing and analyzing the activities of the II International Congress on High Performance Sports, an event hosted by Universidad Santo Tomas and the High Performance Center, Government of Chile. Results. Three of the 15 plenary conferences and one of the 16 workshops focused on martial arts and combat sports. Conclusions. The conference was attended by four professionals from martial arts and combat sports, of note was the presence of Dr. Emerson Franchini. This shows that applied science in martial arts and combat sports is gaining traction within scientific events in the Chilean context, allowing the scientific community to learn about advances related to performance in combat sports. © Idōkan Poland Association.
Keywords: congress; martial arts; combat sports; scientific events; scientific research; training